2003
DOI: 10.4049/jimmunol.171.8.4195
|View full text |Cite
|
Sign up to set email alerts
|

The Rac-Activating Toxin Cytotoxic Necrotizing Factor 1 Oversees NK Cell-Mediated Activity by Regulating the Actin/Microtubule Interplay

Abstract: The cell cytoskeleton is widely acknowledged as a master for NK cell function. Specifically, actin filaments guide the NK cell binding to target cells, engendering the formation of the so-called immunological synapse, while microtubules direct the killer behavior. All these cytoskeleton-dependent activities are competently governed by the Rho GTPases, a family of regulatory molecules encompassing the three different subfamilies, Rho, Rac, and Cdc42. By using a Rac GTPase-activating bacterial protein toxin from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…The small Rho GTPase CDC42 predominantly drives Fasstimulated membrane traffic in T cells, for the following reasons: 1) it promotes the selective traffic of GPI-anchored proteins such as CD59 (Sabharanjak et al, 2002;Mayor and Pagano, 2007), which we found to be rapidly altered after Fas activation (Figures 4 -7); 2) it is activated early after Fas stimulation (Subauste et al, 2000), as confirmed in our experiments (unpublished data); 3) it is selectively inhibited by the semisynthetic compound secramine A (Pelish et al, 2006), which abolishes the alteration of CD59 traffic ( Figures 6 and 7); 4) it is upstream of Rac in promoting filopodia and other surface protrusions, which are blocked by C. difficile toxin B (Malorni et al, 2003), together with the reduction in CD59 traffic alterations ( Figure 6); 5) it is the central regulator of cell polarity (Etienne-Manneville, 2004), and we found that Fas stimulation increases the polarization of membrane traffic toward the Golgi region (Figures 2-7); and 6) when expressed in its constitutively active form, it promotes cell death in Jurkat cells (Chuang et al, 1997), and we found that its inhibition with secramine reduces incipient cell death ( Figure 9C).…”
Section: Fas-enhanced Endocytosissupporting
confidence: 72%
“…The small Rho GTPase CDC42 predominantly drives Fasstimulated membrane traffic in T cells, for the following reasons: 1) it promotes the selective traffic of GPI-anchored proteins such as CD59 (Sabharanjak et al, 2002;Mayor and Pagano, 2007), which we found to be rapidly altered after Fas activation (Figures 4 -7); 2) it is activated early after Fas stimulation (Subauste et al, 2000), as confirmed in our experiments (unpublished data); 3) it is selectively inhibited by the semisynthetic compound secramine A (Pelish et al, 2006), which abolishes the alteration of CD59 traffic ( Figures 6 and 7); 4) it is upstream of Rac in promoting filopodia and other surface protrusions, which are blocked by C. difficile toxin B (Malorni et al, 2003), together with the reduction in CD59 traffic alterations ( Figure 6); 5) it is the central regulator of cell polarity (Etienne-Manneville, 2004), and we found that Fas stimulation increases the polarization of membrane traffic toward the Golgi region (Figures 2-7); and 6) when expressed in its constitutively active form, it promotes cell death in Jurkat cells (Chuang et al, 1997), and we found that its inhibition with secramine reduces incipient cell death ( Figure 9C).…”
Section: Fas-enhanced Endocytosissupporting
confidence: 72%
“…The evidence presented clearly demonstrates that CNF1 is able to perturb the physiological actin cytoskeleton organization in myogenic cells, as occurs in other cell types, 20,21 and to dramatically impair myotube formation upon differentiative stimuli. (e-h) Fluorescence microscopy analysis of C2C12 cells co-stained with fluoresceine-conjugated-phalloidin, to define F-actin organization, and with the nuclear dye DAPI.…”
Section: Cnf1 Hinders Myotube Formation In C2c12 Cellsmentioning
confidence: 99%
“…In the presence of a high concentration of serum, these cells proliferate as an undifferentiated population, while following serum deprivation they permanently withdraw from the cell cycle, undergo terminal differentiation and fuse into multinucleated myotubes. It is known that CNF1 causes an impressive rearrangement of the actin cytoskeleton in most cell lines studied so far, 20,21 thus representing an extremely powerful tool to study those cellular functions that rely on actin network dynamics. Hence, our investigation started by analyzing the effects of CNF1 on the ultrastructure and actin cytoskeleton organization of C2C12 cells, being the cytoskeleton architecture crucial during the muscle cell differentiation.…”
Section: Cnf1 Hinders Myotube Formation In C2c12 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the chemokine CXCL12 (SDF-1␣) induces Rac activation that mediated microvillar breakdown, leading to T lymphocyte emigration and a fruitful NK cell activity and polarization state (10). CXCL12 also controls efficient up-regulation of the integrin 41-dependent T lymphocyte adhesion (11).…”
mentioning
confidence: 99%